EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) DISERTAI FISHBONE DIAGRAM (FD) UNTUK MEMBERDAYAKAN KEMAMPUAN MENGANALISIS - Prasasti, Pinkan Amita Tri (Premiere Educandum, 2015)
The purpose of this study was to determine the effectiveness of a problem based learning model accompanied with Fishbone Diagram to empower the ability to analyse. This study was a quasi-experimental study. The study used a one-group pretest-posttest design. The population of the study was all students of grade X of Public Senior High School 2 Karanganyar in the academic year of 2013/2014. Sample was taken using cluster random sampling technique with a sample of 36 students. The instrument used was questionnaire, observation sheets, interviews, and tests. The ability to analyze data was tested with the Wilcoxon test and calculated by Ngain. The results showed the effectiveness of PBL module accompanied with FD, in which it had been successful in increasing the ability to analyse with a value of Ngainof 0.71 and the result was significance at p = 0.000, making the ability belong to âhighâ category. Based on the results of research and hypothesis testing, it can be concluded that PBL model with FD was effective in empowering the ability to analyseof the tenth graders of.Â Keywords: Problem Based Learning (PBL), Fishbone Diagrams (FD), Ability to analyse